Iso-solvation effects in mixtures of ionic liquids on the kinetics of a model SNAr reaction. (17th October 2017) - Alarcón-Espósito, J.; Contreras, R.; Campodónico, P. R.
Abstract : The SN Ar reaction between 1-chloro-2, 4-dinitrobenzene and morpholine was used as a model system to study solvation effects in a series of mixtures involving imidazolium based ionic liquids. Abstract : The SN Ar reaction between 1-chloro-2, 4-dinitrobenzene and morpholine was used as a model system to study solvation effects in a series of mixtures involving imidazolium based ionic liquids. Iso-solvation regimes ( i.e. a solvent composition regime where the solute is being solvated by approximately the same number of different solvent molecules in the mixture) are reported for the first time in ionic liquid mixtures, for 4 mixtures including [EMIM][SCN][DCN], [BMIM][DCN][BF4 ], [BMIM][BF4 ][PF6 ] and [BMIM][PF6 ][FAP]. The results show that for significant changes in composition, the rate coefficients remain approximately constant. An additional interesting result is that the mixture [BMIM][BF4 ][PF6 ] (in the proportion of 0.9 for the molar fraction of BMIMBF4 ) shows a slightly better kinetic performance as compared to pure BMIMBF4 and BMIMPF6 . Finally, for the [EMIM][SCN][DCN] mixture, an increasing proportion of EMIMSCN with respect to EMIMDCN results in a decrease in the rate coefficient within the range of {0.1–0.75} for the molar fraction of EMIMSCN. This result may be traced to competition between the anions [SCN − ] and [DCN − ] towards the reaction center driven by the basicity of the reaction medium.